Synthesis and Pharmacological Evaluation of (6-Substituted 4-Oxo-4H-chromene-3 yl) methyl N-substituted Aminoacetates - Gajbhiye, Asmita (Medknow Publications, 2008)
A series of the title compounds were synthesized and characterized by spectral data. All the compounds were evaluated for in vitro antihistaminic activity by inhibition of isotonic contractions induced by histamine on isolated guinea pig ileum and the compound 6-k showed significant activity. A few compounds have also been screened for in vivo bronchodilatory activity. These compounds exhibited significant protection against histamine-induced convulsions in guinea pig at the dose of 50 μmol.